The necessity to create Europeanness : a critical review of European Schools’ education project - Zuccarello, Silvia (2021)
This research is a qualitative study of the European Schools’ (ES) educational system. It was conducted from a social constructionist viewpoint, according to which language is seen as social action. ES are schools which were founded with the rise of the first European institutions to educate the children of EU’s diplomats relocating within Europe. The initial aim was to ensure these children had a linear leaning experience. Today, ES became schools accessible to other pupils of Europe, with the aim of developing their European identity through a multilingual and multicultural education project. In this work I wanted to examine power discourses within ES educational mission, by specifically looking at the rhetoric of solidarity, Europeanness, and cultural diversity. The research was data-driven and used Critical Discourse Analysis to answer the question: How are the ES educational mission and learning practices constructed in the language of ES official documents? The data consisted of thirteen texts among which policy documents, curricula, and syllabuses. These texts are considered crucial means to track the change and developments of ES learning practices. In fact, studying official documents helped giving meaning, developing an understanding and discovering insights relevant to the research problem. The ES education project and the notion of European identity are constructed through six meta-discourses. These are (1) Essentialist understandings of identity and culture, (2) Absence of pupils’ interaction and of interaction among ES and other schools, (3) Majority-centered discourses about diversity, (4) Educational elitism, Eurocentrism, and European exceptionalism, (5) Absence of definitions and persuasive narrative, (6) Economic and political discourses. The identification of these discourse patterns showed that texts can be very powerful means for the legitimization of political, economic, social objectives, such as recreating an image of a united Europe. I concluded that ES’ educational system is a crucial vehicle of transmission of EU’s political, economic, and social ideologies.